Monosaccharide and Chitin Content of Cell Walls of Histoplasma capsulatum and Blastomyces dermatitidis - Domer, Judith E. (1971)
Cell walls of Histoplasma capsulatum and Blastomyces dermatitidis, obtained by mechanical breakage of yeast- and mycelial-phase cultures, were lipid-extracted and then fractionated with ethylenediamine. Unextracted cell walls, lipid-extracted cell walls, and the three fractions resulting from ethylenediamine treatment were examined for monosaccharide and chitin content. The yeast-phase cell walls of five strains of H. capsulatum fell into two categories, designated chemotypes I and II, one of which, chemotype II, was similar to yeast-phase cell walls derived from three strains of B. dermatitidis. H. capsulatum chemotype I cell walls were characterized by lower content of material soluble in ethylenediamine, higher chitin content, and lower monosaccharide content than H. capsulatum chemotype II or B. dermatitidis cell walls. Approximately 80% of the monosaccharides of chemotype I cell walls was combined in forms susceptible to attack by mild acid hydrolysis, compared with about 50% of the monosaccharides of chemotype II and B. dermatitidis. H. capsulatum and B. dermatitidis yeast-phase cell walls could be distinguished, however, by their susceptibility to attack by a crude enzyme system derived from a Streptomyces sp. incubated with chitin as the only carbon source. Both glucose and acetylglucosamine were released from H. capsulatum cell walls, regardless of chemotype, during enzymatic hydrolysis, whereas only acetylglucosamine was released from B. dermatitidis yeast-phase cell walls. Mycelial-phase cell walls of H. capsulatum and B. dermatitidis were characterized by lower content of material soluble in ethylenediamine, higher proportions of mannose, and lower chitin content than their respective yeast phases. Glucose and acetylglucosamine were both released from all mycelial-phase cell walls, whether H. capsulatum or B. dermatitidis, by the crude enzyme system.